A study on door motifs in Medina Tunisia (12th -19th century): motif designs and meanings / Abdelaziz Gattoufi - Gattoufi, Abdelaziz (2015)
The purpose of this research is to analyse and understand the traditional doors motifs in Tunisia. Through time this treasured heritage is becoming endangered. In conjunction, this study is aimed to explore and identify the application of motifs and decorated elements on doors especially in Medina of Tunis. The objective of this study is to identify the types of traditional doors motifs and decorated elements. Besides that it is also to determine the symbolic interpretation and the philosophy of the motifs on doors. This research use qualitative methodology in which it was conducted by reviewing the literature on the topic, observation and interviews. Data was also obtained by collecting samples and traditional motifs of each artwork. Traditional doors were observed through a significant change; especially in terms of design where doors motifs are no longer applied. The collected motifs were shown to be an effective way of documenting the Tunisian national treasure of traditional doors motifs in each creation of arts before its extinction